Novel GRHL3 Variants in a South African Cohort With Cleft Lip and Palate. (September 2022) - Naicker, Thirona; Adeleke, Chinyere C.; Alade, Azeez; Mossey, Peter A.; Awotoye, Waheed A.; Busch, Tamara D.; Li, Mary; Olotu, Joy; Gowans, Lord J. J.; Aldous, Colleen; Butali, Azeez
Objective: The etiology of cleft palate (CP) is poorly understood compared with that of cleft lip with or without palate (CL ± P). Recently, variants in Grainyhead like transcription factor 3 ( GRHL3 ) were reported to be associated with a risk for CP in European and some African populations including Nigeria, Ghana, and Ethiopia. In order to identify genetic variants that may further explain the etiology of CP, we sequenced GRHL3 in a South African population to determine if rare variants in GRHL3 are associated with the presence of syndromic or nonsyndromic CP. Design: We sequenced the exons of GRHL3 in 100 cases and where possible, we sequenced the parents of the individuals to determine the segregation pattern and presence of de novo variants. Setting: The cleft clinics from 2 public, tertiary hospitals in Durban, South Africa (SA), namely Inkosi Albert Luthuli Central Hospital and KwaZulu-Natal Children's Hospital. Patients, participants: One hundred patients with CL ± P and their parents. Interventions: Saliva samples were collected. Main outcome measures: To ascertain the genetic variants in the GRHL3 gene in patients with CL ± P in SA. Results: Five variants in GRHL3 were observed; 3 were novel and 2 were known variants. The novel variants were intronic variants (c.1062 + 77A>G and c.627 + 1G>A) and missense variant (p.Asp169Gly). Conclusions: This study provides further evidence that variants in GRHL3 contribute to the risk of nonsyndromic CP in African populations, specifically, in the South African population.